185 A MULTICOMPONENT MODEL CAN PREDICT OUTCOME OF RESTRICTIVE SURGERY FOR OBESITY. (1st January 2006) - Aslam, N.; Rashed, H.; Madan, A. K.; Tichansky, D. S.; Cutts, T.; Johnson, W. D.; Abell, T.
Abstract : Introduction: We previously reported that a multicomponent model of autonomic and enteric factors may correlate with ultimate weight loss or gain after restrictive obesity surgery (Neurogastroenterol Motil abstract, 2005). Patients: We have followed 39 patients (10 gainers, 29 losers), 4 male, 35 female, mean age = 37.2 years, who underwent vertical banded gastroplasty, for up to 15 years post surgery, evaluating ultimate weight loss (losers) or gain (gainers). Patients were compared with their latest available weight vs baseline weight. Baseline autonomic (adrenergic: photophlethesmotic VC and PAR and cholinergic: EKG RRI) and enteric measures (electrogastrogram: EGG), as previously reported, above, were compared with latest weight. Methods: We performed a discriminant function analysis to investigate whether a patient's EGG, PAR, RRI, and VC values could be used to classify that patient as a loser or gainer following weight control surgery. The patients were divided into two groups (the gold standard for gainers or losers). The discriminant criterion derived from the data for patients in the two groups was applied to each patient's EGG, PAR, RRI, and VC values to determine whether these measurements separated the patients into their gold standard category. Results: A model based on baseline measures successfully predicted ultimate weight gain in 8/10 (80%) patients who subsequently gained weight and weight loss in 24/29 (83%) patients who subsequently lost weight for a total correct classification rate of 32/39 (82%) (see table below). Conclusions: A multicomponent model shows that baseline measures can predict ultimate weight outcome from restrictive obesity surgery.